PERIODICAL PROPERTY IN THE NEW CIVIL CODE - Mihaela, Cojan (Anales Universitatis Apulensis Series Jurisprudentia; No 15 (2012): ANNALES UNIVERSITATIS APULENSIS - SERIES JURIPRDENTIA, 2012)
The characteristic of periodical property is that more than one person should exert successively and repetitively the attribute of use specific to the right of property on a mobile or immobile asset, during determined time intervals, whether equal or unequal. Periodical property is regulated by the New Civil Code as a variety of imposed joint property, and not as an absolute modality of property. What is peculiar to periodical property is the way of expressing the intellectual division of the right, the shares being expressed in periods of time. This peculiarity makes the attribute of use to be exerted differently by the owners of periodical property compared to the titular co-holders of a shared quota of the right. In the time span in which in which a co-owner has the right of use on the asset, he or she will solely and exclusively exert this prerogative on the asset as a whole. The use of the asset is successive and repetitive, on determined intervals which may be equal or unequal. Key-words: Periodical property, imposed joint property, the attribute of use, shared quotas expressed in time intervals.